Synergistic potential of natural products and exercise: unveiling molecular mechanisms and innovative therapeutic approaches for liver diseases - Ye, Qi; Yuan, Shoudu; Cai, Deliang (Frontiers in Nutrition, 2025)
Liver diseases, particularly non-alcoholic fatty liver disease (NAFLD) and metabolic dysfunction-associated steatotic liver disease (MASLD), have grown to be significant global health issues. These conditions are strongly associated with metabolic syndrome, obesity, and diabetes. The management of chronic illnesses still necessitates lifestyle changes, such as improved diet and increased physical activity, despite advances in pharmaceutical therapies. With their numerous bioactive constituents, natural products have shown significant hepatoprotective effects through lipid metabolism, oxidative stress, and inflammatory modulation. Key natural substances, including resveratrol, curcumin, and silymarin, have demonstrated potential in clinical and experimental settings by influencing molecular pathways essential to liver health. Simultaneously, exercise interventions, specifically resistance and aerobic training, have successfully improved insulin sensitivity, decreased intrahepatic fat, and enhanced metabolic performance. Recent research suggests that the combined use of natural products and exercise represents a novel therapeutic approach. This approach may offer a therapeutic synergy that targets underlying biological mechanisms and circumvents some of the limitations of existing therapies. Furthermore, probiotic-induced microbiota modification and the gut-liver axis provide new perspectives on the holistic treatment of liver disease. This review underscores the urgent need for more studies to maximize integrative therapy approaches, identifies current research gaps, and summarizes recent developments on the combined effects of exercise and natural products in preventing and treating liver disease. These revelations open the door to creative treatments that enhance liver health and lessen the prevalence of liver illnesses worldwide, highlighting the crucial role of further research in this field.